Delayed manifestation of proliferative retinopathy associated with chronic myeloid leukemia - Alan Chew Bonilla; Paulina Bueno Zarazúa; Jaime Rosales Padron; Emiliano Fulda Graue; Federico Graue Wiechers (American Journal of Ophthalmology Case Reports)
Purpose: This report highlights a rare case of delayed manifestation of proliferative retinopathy associated with chronic myeloid leukemia (CML) during remission. Observations: Case report and review of the literature; In this case report, we outline the delayed manifestation and clinical progression of proliferative retinopathy in a 52-year-old male patient with a history of CML diagnosed in 2001. Initially, the patient presented with a white blood cell count (WBC) of 402,200/μl, and the leukocytosis persisted until 2005. Thereafter, the patient remained in remission for over 15 years without any visual complaints until 2022. At that time, the patient sought medical attention due to a ten-day history of left eye visual impairment, leading to the discovery of peripheral neovascularization in both eyes and vitreous hemorrhage in the left eye during fundus examination. The WBC count at the time of presentation to the Emergency Department was 10,460/μl. The patient was treated with fluorescein angiography guided panretinal photocoagulation to the areas of ischemic retina. Subsequent follow-up after eight months demonstrated regression of neovascularization. Conclusions and Importance: Our findings highlight the occurrence of proliferative retinopathy in the context of CML, uniquely manifesting during remission. This case emphasizes the importance of ophthalmological assessments not only at the time of CML diagnosis but also during subsequent follow-ups, recognizing the potential for delayed presentation of ocular complications.